The Effect of Egg White Consumption on the Healing of Perineal Wounds in Post Partum Mothers at Harjono Ponorogo Hospital - Yustina Purwaningsih; Wiwiek Retti Andriani (Health Notions, 2022)
Postpartum period is a period of reproductive organs recovery that undergoing major changes during pregnancy and childbirth, for example perineal tear recovery. Acceleration of perineal wound healing during the postpartum period is expected to prevent postpartum mother from infection. The research aimed to determine the effect of egg white consumption on the healing of perineal wounds in post partum mothers at  Harjono Ponorogo Hospital. The research method is experiment with a population of postpartum mothers who suffered perineal wounds at Dr. HarjonoPonorogo Hospital, The sample in this research were 51 respondents which were divided into 3 groups, namely the control group, the first case group was giving 5 egg whites per day for 6 days  and the second case group was giving 3 egg whites per day for 6 days. Each group consists of 17 respondents. Then the sample were analyzed using the che square statistical test. The results of the research is P volue 0.022 < from α 0.05. The result showed that there is a positive influence of egg white consumtion on postpartum maternal perineal wound healing. It is recommended for postpartum mothers to consume at least 3 egg whites a day to speed up the healing process of perineal wounds.Keywords: egg white; perineal wound healing; postpartum mothers